2014
DOI: 10.1530/eje-13-0802
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between endogenous testosterone and lipid profile in middle-aged and elderly Chinese men

Abstract: Objective: To evaluate the relationship between serum total testosterone (TT) level and lipid profile after adjusting for some traditional confounding factors, free thyroid hormones and TSH in Chinese men. Methods: This was a retrospective study based on an epidemiological investigation including 11 000 subjects. Bivariate and partial correlation analysis, multiple linear regression analysis, and a general linear model were used to assess the influence of TT on the lipid profile. Additionally, the odds ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 49 publications
5
38
0
1
Order By: Relevance
“…Conversely, high levels of testosterone are related to favorable cardiovascular risk profile [4]. Furthermore, an inverse relationship between testosterone and atherogenic lipid profile including total cholesterol, LDL-cholesterol and triglycerides has been demonstrated, while the association of HDL cholesterol with testosterone is positive [5]. Expanding further these observations, we recently showed that low plasma testosterone is associated with adverse cardiovascular outcomes in middle-aged hypertensive patients [6].…”
Section: Introductionmentioning
confidence: 79%
“…Conversely, high levels of testosterone are related to favorable cardiovascular risk profile [4]. Furthermore, an inverse relationship between testosterone and atherogenic lipid profile including total cholesterol, LDL-cholesterol and triglycerides has been demonstrated, while the association of HDL cholesterol with testosterone is positive [5]. Expanding further these observations, we recently showed that low plasma testosterone is associated with adverse cardiovascular outcomes in middle-aged hypertensive patients [6].…”
Section: Introductionmentioning
confidence: 79%
“…Blood samples were obtained from all the subjects from 8:00 to 10:00 after a minimum 10-h overnight fast [9, 38, 39]. Serum TSH, FT3, FT4, FSH, LH, T, ACTH and COR levels were determined by chemiluminescent methods (Roche, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Testosterone deficiency is thought to promote atherosclerosis by modulating lipid metabolism [8]. Several clinical and epidemiological studies have reported that serum testosterone levels are inversely correlated with total cholesterol and LDL cholesterol levels [9-11]. Moreover, animal studies have also demonstrated markedly increased serum cholesterol levels in testosterone-deficient male mice [12,13].…”
Section: Introductionmentioning
confidence: 99%